Social protection systems in the EU: financing arrangements and the effectiveness and efficiency of resource allocation (Luxembourg, 2015)
"This report provides a comprehensive overview of how social protection systems in the EU are financed. It examines the sources and structures of this financing, along with how money is spent and resources allocated. Finally, the document addresses the question of the effectiveness and efficiency of the systems in place and also provides country overviews and relevant data. This publication is available online in English."